Keberadaan Ephemeroptera, Plecoptera, Trichoptera (EPT) Sebagai Bioindikator Pencemaran di Sungai Bone Gorontalo - Kadim, Miftahul Khair; Pasisingi, Nuralim; Polamolo, Ade Irma; Maharani, Siti Adel (Jurnal Sumberdaya Akuatik Indopasifik, 2025)
Rivers play a crucial role as aquatic ecosystems within the hydrological cycle, serving as vital areas for environmental water absorption. Their conditions are intricately shaped by both human activities and the inherent characteristics of their surrounding environments. Among these rivers, the Bone River stands as a pivotal hub of community life in Gorontalo, yet it faces significant vulnerability to pollution. This research endeavors to assess the water quality of the Bone River utilizing Ephemeroptera, Plecoptera, and Trichoptera (EPT) as bioindicators. Conducted between March and April 2021, the study spanned eight carefully selected observation stations, covering the river's course from upstream to downstream. The evaluation of water quality is undertaken through a quantitative analysis of biotile diversity parameters, encompassing calculations of EPT diversity, percentage abundance, and the overall diversity of macrozoobenthos families. From the research findings, it was revealed that the Bone River hosts 16 EPT families, comprising a total of 1438 individual observations. Across the eight stations, the diversity of the EPT family encompassed 16 taxa, inclusive of 7 Ephemeroptera and 9 Trichoptera taxa, with Plecoptera notably absent. Notably, the results of the Biotilik examination yielded a score of 2.28 for the water quality of the Bone River. This score indicates a pollution burden on the river, as evidenced by elevated Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) concentrations at select observation sites, surpassing established quality standards. Furthermore, the absence of macrozoobenthos, particularly Plecoptera, which are known for their sensitivity to pollution, further underscores the compromised state of the river's water quality.